Stroke Patients With Faster Core Growth Have Greater Benefit From Endovascular Therapy. Issue 12 (December 2021) - Lin, Longting; Zhang, Hao; Chen, Chushuang; Bivard, Andrew; Butcher, Kenneth; Garcia-Esperon, Carlos; Spratt, Neil J.; Levi, Christopher R.; Parsons, Mark W.; Li, Gang
Abstract : Background and Purpose: This study aimed to explore whether the therapeutic benefit of endovascular thrombectomy (EVT) was mediated by core growth rate. Methods: This retrospective cohort study identified acute ischemic stroke patients with large vessel occlusion and receiving reperfusion treatment, either EVT or intravenous thrombolysis (IVT), within 4.5 hours of stroke onset. Patients were divided into 2 groups: EVT versus IVT only patients (who had no access to EVT). Core growth rate was estimated by the acute core volume on perfusion computed tomography divided by the time from stroke onset to perfusion computed tomography. The primary clinical outcome was good outcome defined by 3-month modified Rankin Scale score of 0–2. Tissue outcome was the final infarction volume. Results: A total of 806 patients were included, 429 in the EVT group (recanalization rate of 61.6%) and 377 in the IVT only group (recanalization rate of 44.7%). The treatment effect of EVT versus IVT only was mediated by core growth rate, showing a significant interaction between EVT treatment and core growth rate in predicting good clinical outcome (interaction odds ratio=1.03 [1.01–1.05], P =0.007) and final infarct volume (interaction odds ratio=−0.44 [−0.87 to −0.01], P =0.047). For patients with fast core growth of >25 mL/h, EVT treatment (compared with IVT only) increased the odds of good clinical outcome (adjusted odds ratio=3.62 [1.21–10.76], P =0.021) and resulted in smaller final infarction volume (37.5 versus 73.9 mL, P =0.012). For patients with slow core growth of <15 mL/h, there were no significant differences between the EVT and the IVT only group in either good clinical outcome (adjusted odds ratio=1.44 [0.97–2.14], P =0.070) or final infarction volume (22.6 versus 21.9 mL, P =0.551). Conclusions: Fast core growth was associated with greater benefit from EVT compared with IVT in the early <4.5-hour time window. Abstract : Supplemental Digital Content is available in the text.